Farabi's contribution to the architecture of Central Asia. (Journal of Architectural Design, 2021)
It is our sacred duty to preserve the priceless treasures left to us by scientists who lived and worked in the past. In particular, the fact that Farabi's studies of the laws of society and nature have not yet been fully elucidated encourages us to work and research more. This article discusses Farabi's ideas about geometric constructions and measurements.